The “matser” made world: a new conceptualization of matter and spirit - Socrates Ebo (Cхід, 2019)
The world has always been, and will always be a fascinating enigma to man. Generations of thinkers have struggled to fathom the world and explain it in an intelligible formation. Till date, a thoroughly satisfactory explanation of the cosmos has not been finagled. The search for a comprehensive explanation of the world continues. Dominating the interpretations of the world are the materialistic and idealistic schools of thought. These are diametrically opposed cosmological systems without a middle ground. The materialists see the world as essentially material, devoid of any god or maker. The idealists see the world as a product of a spirit or mind. They believe the world to be fundamentally non-material in nature. Nkrumah, a thorough going materialist, believes the world to be fundamentally material in nature, Berkeley who was the most radical advocate of idealism, however, believes the world to be fundamentally spiritual. But the cosmos is, irrespective of man’s interpretation of it. It is fundamentally one in our experience. The problem lies with our conception of some phenomena as material; and some others as spiritual. How can the material and non-material interact? If the world is material, it is definitely not spiritual. If it is made of ideas only, it is definitely not material. But supposing the world is neither material nor spiritual? It could as well be that our definition of matter does not encompass some of the properties inherent in the phenomena we regard as ‘matter”. It could as well be that what we refer as “spiritual” are properties inherent in but not encompassed by the definition of what we call matter. We could as well be living in a “matserial” cosmos, a world that is fundamentally made up of substances whose properties include those we conceive as “material” and some of those we consider as “spiritual”. Perhaps it is time to re-examine our concept of matter and our concept of spirit. Perhaps, we should be talking of “matser” rather than matter and spirit. This work is a product of library research, philosophical analysis and systematic philosophical speculation. It addresses the problem of the interpretation of the world which encompasses the problem of language and the mind/matter dichotomy. It is the finding of this work that the cosmos is neither made up solely of matter or spirit. Phenomena exhibit characteristics which we traditionally describe as spiritual and material. Our conceptualizations of mind and spirit logically leads to a dual cosmos of mind and spirit, which obviously is fallacious. We are in one cosmos. The cosmos is only doubled in our language, not in our experience. Our experience of the cosmos remains one. It is the recommendation of this work that “matser” rather than mind and spirit should be used to characterize phenomena. Ours is a matserial cosmos.